Attenuated Glial K+ Clearance Contributes to Long-Term Synaptic Potentiation Via Depolarizing GABA in Dorsal Horn Neurons of Rat Spinal Cord - 이재광; Oleg V Favorov; Mark Tommerdahl; Barry L. Whitsel; 이창준 (한국뇌신경과학회, 2014)
synaptic transmission underlies central sensitization, secondary hyperalgesia, and persistent pain. We tested whether impaired clearance of K+ and glutamate by glia in DHs may contribute to initiation and maintenance of the CNS pain circuit and sensorimotor abnormalities. Transient exposure of the spinal cord slice to fluorocitrate (FC) is shown to be accompanied by a protracted decrease of the DHs optical response to repetitive electrical stimulation of the ipsilateral dorsal root, and by a similarly protracted increase in the postsynaptic response of the DHs like LTP. It also is shown that LTPFC does not occur in the presence of APV, and becomes progressively smaller as [K+]o in the perfusion solution decreased from 3.0 mM to 0.0 mM. Interestingly LTPFC is reduced by bath application of Bic. Whole-cell patch recordings were carried out to evaluate the effects of FC on the response of DHs neurons to puffer-applied GABA. e observations reveal that transient exposure to FC is reliably accompanied by a prolonged (>1 hr) depolarizing shi of the equilibrium potential for the DHs neuron transmembrane ionic currents evoked by GABA. Considered collectively, the findings demonstrate that LTPFC involves (1) elevation of [K+]o in the DHs, (2) NMDAR activation, and (3) conversion of the effect of GABA on DHs neurons from inhibition to excitation. It is proposed that a transient impairment of astrocyte energy production can trigger the cascade of dorsal horn mechanisms that underlies hyperalgesia and persistent pain.